Signaling Pathway and Small-Molecule Drug Discovery of FGFR: A Comprehensive Review - Zheng, Jia; Zhang, Wei; Li, Linfeng; He, Yi; Wei, Yue; Dang, Yongjun; Nie, Shenyou; Guo, Zufeng (Frontiers in Chemistry, 2022)
The targeted therapy is a groundbreaking innovation in cancer treatment. Among the receptor tyrosine kinases, the fibroblast growth factor receptors (FGFRs) garnered enormous attention as promising therapeutic targets due to their fundamental biological functions and high frequency of abnormality in tumors. In the past two decades, several generations of FGFR kinase inhibitors have been developed. In this review, we introduced the biological basis of FGF/FGFR signaling and summarized the small-molecule FGFR inhibitors which were categorized into several types according to modes of action, meanwhile small-molecule-based therapies of different modalities were systematically described. We also shared our perspectives for the development of novel FGFR inhibitors.